Entrepreneurial Motivation of Islamic Young Generation - Jihan Miranda; Marlya Fatira AK; Muhammad Zuhirsyan (Journal of Trends Economics and Accounting Research, 2020)
This article describes the motivation to be entrepreneurial in the younger generation of Muslims studying at the Medan State Polytechnic campus. Sources of data in this study are primary data sources obtained from questionnaires distributed to students of the Medan State Polytechnic Accounting Department via a google form. The type of data in this study is quantitative, qualitative data using a Likert scale. The data collection technique used a questionnaire, which was distributed to 204 respondents. The data analysis technique used linear regression analysis, correlation coefficient, and partial test (t statistical test). The results of this study indicate that the entrepreneurial motivation of the younger generation of Muslims who are currently undergoing education at campus significantly affects their entrepreneurial activities. Students are motivated by enthusiasm, creativity, and innovation, dare to take risks, and will be interested in doing entrepreneurial activities during their study period on campus.